Sosialisasi Teknologi Tepat Guna Bidang Tanaman Produktif di Desa Antap Kecamatan Selemadeg Kabupaten Tabanan - Wiasti, N. M.; Dhana, I. N.; Wirawan, A. A. B.; Sukardja, P. (Buletin Udayana Mengabdi, 2015)
This community service activity is meant to provide motivation for farmers at Antap village in order that they can cultivate crops by using technology effectively. To that end, the concrete measures taken are by providing knowledge and understanding to their characteristics and how to utilize the appropriate technology in the areas of productive plants, particularly crops. Technically, this activity was conducted by making a discussion with all the participants. In addition, relevant reading materials are also given to all participants of this activity. In the discussion is reviewed some matters related to the appropriate technology in the field of productive plants by providing concrete examples so that participants can be expected to obtain a broad and deep understanding. To strengthen the understanding and be able to be followed up with practices, so the subject of discussion is equipped with handy hints about the ins and outs of the appropriate technology. Results of these activities can be concluded that all the participants of the socialization on appropriate technology in the field of productive crop are interested in the socialization material, even though they already have a certain knowledge and unpleasant experience in the context of the planting crop activities with the use of a particular technology. It is evident from their serious attitude and vivacity, both in the implementation of the approach to them and in the implementation of discussion on the appropriate technology in the field of productive plants.
Keywords: appropriate technology, productive plants, an increase in production